Toxocara seroprevalence among clinically healthy individuals, pregnant women and psychiatric patients and associated risk factors in Shandong Province, Eastern China. - Wei Cong; Xiao-Xuan Zhang; Na Zhou; Chang-Zheng Yu; Jia Chen; Xiang-Yang Wang; Bing Li; Ai-Dong Qian; Xing-Quan Zhu (Public Library of Science (PLoS), 2014)
Toxocarosis is a widespread zoonosis caused by the ascarid nematodes Toxocara canis and Toxocara cati, which primarily infect dogs and cats, respectively. Most human infections with Toxocara are asymptomatic; however, some infected individuals may develop a serious illness and even death. Nevertheless, epidemiological knowledge regarding the prevalence and risks associated with Toxocara infection is limited in China. Therefore, we performed a cross-sectional pilot study and estimated the seroprevalence of Toxocara infection in humans in Shandong Province, eastern China for the first time, from June 2011 to July 2013, involving clinically healthy individuals, pregnant women and psychiatric patients, aiming to attract public attention to Toxocara infection.Seroprevalence of Toxocara was determined using an enzyme-linked immunosorbent assay based on a cross-sectional study conducted in Qingdao and Weihai, Shandong Province, eastern China. Factors potentially associated with Toxocara infection were identified by logistic regression analysis. The overall Toxocara seroprevalence among the study population (n = 2866) was 12.25%, and a significantly higher seroprevalence in psychiatric patients (16.40%, 73/445) than that in clinically healthy individuals (13.07%, 187/1431) and pregnant women (9.19%, 91/990) was revealed. Univariate analyses suggested that keeping dogs at home (OR = 0.06, 95% CI 0.05-0.08, P<0.001), contact with cats and dogs (OR = 0.42, 95% CI 0.33-0.53, P<0.001) and exposure with soil (OR = 0.37, 95% CI 0.28-0.49, P<0.001) were risk factors associated with Toxocara infection.The present study revealed, for the first time, that human infection with Toxocara is common in eastern China, posing a significant public health concern. Increasing human and dog populations, population movements and climate change all will serve to increase the importance of this zoonosis. Further studies under controlled conditions are necessary to define potential morbidity associated with Toxocara infection.